Pengaruh Paylater Dan Hedonic Shopping Motivation Terhadap Impulse Buying Dan Minat Beli Ulang - Windi Eka Wulandari; Kholid Murtadlo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research was conducted to determine the effect of the paylater and hedonic shopping motivation features on impulse buying and repurchase intention in Generation Z e-commerce Shopee users in Pasuruan Regency. This research was conducted on generation Z in Pasuruan district using the Shopee e-commerce, in 2023. The data collection technique used was a questionnaire which was distributed online via the Google form. The sample used in the study was 114 respondents with a purposive sampling method, namely determining the sample in which the people selected as the sample are in accordance with the purpose of conducting the research. In processing this research data is done by using the method of path analysis (Path Analysis).